2004
DOI: 10.1242/jeb.00971
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of different NaPi cotransporter isoforms to dietary regulation of P transport in the pyloric caeca and intestine of rainbow trout

Abstract: SUMMARY The anatomical proximity and embryological relationship of the pyloric caeca (PC) and small intestine of rainbow trout has led to the frequent assumption, on little evidence, that they have the same enzymes and transporters. In trout, the PC is an important absorptive organ for dietary nutrients, but its role in dietary P absorption has not been reported. We found that apical inorganic phosphate (Pi) transport in PC comprises carrier-mediated and diffusive components. Carrier-mediated up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
6
29
0
Order By: Relevance
“…In case of fish, it is most likely that degradation of IP6 occurs in stomach since the pH of stomach is between 2.0 and 4.0 depending on the species. Sugiura & Ferraris (2004) reported that stomach of rainbow trout filled with feed had pH of chime around 4 and remained at the same unit even 6-9 h after feeding. Similarly, stomach pH of juvenile Japanese flounder after 1 h feeding was around 4.19 and became alkaline in intestine (Laining et al, 2010a).…”
Section: Fluctuation Of Post-prandial Plasma Mineral Level Of Juvenilmentioning
confidence: 98%
“…In case of fish, it is most likely that degradation of IP6 occurs in stomach since the pH of stomach is between 2.0 and 4.0 depending on the species. Sugiura & Ferraris (2004) reported that stomach of rainbow trout filled with feed had pH of chime around 4 and remained at the same unit even 6-9 h after feeding. Similarly, stomach pH of juvenile Japanese flounder after 1 h feeding was around 4.19 and became alkaline in intestine (Laining et al, 2010a).…”
Section: Fluctuation Of Post-prandial Plasma Mineral Level Of Juvenilmentioning
confidence: 98%
“…First, postprandial gastric acidity tends to be low in fish. Our laboratory has shown that when the rainbow trout stomach was filled with food, the pH of the chyme was high and remained high (~4.0) even 6-9·h after feeding (Sugiura and Ferraris, 2004). It is well known that postprandial pH of mammalian stomach can reach 2 or less (Berne and Levy, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…The pellets were dried at room temperature for 1.5·days, stored at 4°C, and fed within 2·weeks. Diets were analyzed for proximate compositions (Table·1) and P and calcium (Ca) concentrations (Table·2) according to the method described previously (Sugiura and Ferraris, 2004).…”
Section: Experimental Dietsmentioning
confidence: 99%
See 2 more Smart Citations